Peering into the unseen: Novel methods in identifying shell taxa from archaeological micro-fragments. (November 2022) - Oertle, Annette; Szabó, Katherine; Gaqa, Sibongiseni; Cawthra, Hayley C.; Esteban, Irene; Pargeter, Justin; Fisher, Erich C.
Abstract: Archaeomalacological analysis is generally undertaken on recovered macro-remains to characterize the overall composition of faunal remains in a deposit. Given the susceptibility of shell middens to a variety of taphonomic processes, it is assumed that the prior presence of shell in deposits may therefore occasionally be missed. Deteriorated micro-remains can mix indistinguishably into surrounding sediments and make their analyses and identification difficult, particularly in older deposits and in environments that experience rapid rates of weathering. This paper explores whether microscopic remains of deteriorated molluscs can be distinguished from other microscopic remains at the coastal rock shelter site of Waterfall Bluff in Mpondoland, South Africa. The methodology uses a multi-scalar approach integrating shell mineralogy and microstructure using the taxonomic distinctiveness of these features. The diagnostic features (e.g., morphology, hinges, spires, and apertures) used for identifying macro-remains are absent in micro-remains, therefore unique methods of identification are needed to identify these microscopic mollusc fragments. Through mineralogical analyses and scanning electron microscope (SEM) imaging, the nacreous remains of Mytilidae shell were identified from previously unidentified degraded shell remains as well as sediment samples from Waterfall Bluff. These methods thus recovered 'invisible' evidence of shellfish remains providing further evidence of continued coastal foraging from Marine Isotope Stage 3 to the early Holocene ( ca or ⁓ 40 ka to 10 ka) on the south-eastern African coast. Highlights: Multi-scalar approach integrating shell mineralogy and microstructure to taxonomically identify micro-shell remains. Highly fragmented and degraded shell remains at WB due to acid dissolution from drip water under the dripline. Nacre tablets identified by Scanning Electron Microscopy in an aggregate with no macro shell evidence. Ostreidae and Mytilidae mollusc shell microstructure and composition examined.